Working through the cinematography of international criminal justice: procedures of law and images of atrocity. Issue 1 (24th August 2018) - Rush, Peter D; Elander, Maria
Abstract: This article addresses legal procedures and the cinematography of film in international criminal justice. The examples range across fiction, documentary, and trial film. The concern is with relations of authority and subjectification within the architecture of the courtroom and before the image. It considers procedures of projection, evidential confrontation and the destruction of the image in the era of the witness.